Prospect of secure-efficient search and privacy-preserving mechanism on big data - Shang LI; Zhi-gang ZHOU; Hong-li ZHANG; Xiang-zhan YU (网络与信息安全学报)
With rapid development of information industry,services related to big data search have permeated into almost every aspect of human lives.Relevant technologies are undergoing profound changes,such as privacy pres-ervation for data fusion,context-aware search intention comprehending and statistic search pattern.The issues of secure-efficient search and privacy-preserving for big data were studied and looked ahead.Firstly,three chief scien-tific problems were refined from the aspects of multi-source data publication,awareness of users’ search require-ments and privacy-aware wise solutions,respectively.Secondly,main research contents were proposed,including big data oriented information fusion and knowledge extraction,granular knowledge representation and inference,interactive representation of search task,user experience driven task management,granular search pattern balancing utility with cost,and secure search mechanism based on differential privacy.Lastly,several promising techniques in future were discussed.